The Influence of Transformational Leadership Characteristics on The Creativity of Employees in The Planning Departement Of CV XYZ - Pradita Nindya Aryandha (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2019)
The non-repetitive work environment of an organization requires more creative employees in order to provide a high quality service. In the construction service sector, the construction planners have to be able to design a building which not only sophisticated but also conceive a standard security level. The leader in a company has an important role to encourage the creativity of employees. This research is aimed to examine and analyze the influence of transformational leadership characteristics on the creativity of employees. Idealized influence, individualized consideration, inspirational motivation and intellectual stimulation are the independent variables while the employees creativity is the dependent variable. The data used in this research was the primary data that acquired through survey method by disseminating questionnaires. About 119 respondents who work as the employee of the planning department of CV XYZ were used in this research. In this research, a multiple regression analysis was used to analyze the influence of transformational leadership characteristics towards the creativity of employees. The research results mention that there are positive and significant influences of each characteristic of transformational leadership, namely idealized influence, individualized consideration, inspirational motivation and intellectual stimulation on the creativity of employees.